2007
DOI: 10.1111/j.1365-2044.2007.05255.x
|View full text |Cite
|
Sign up to set email alerts
|

EEG changes and serum anticholinergic activity measured in patients with delirium in the intensive care unit

Abstract: SummaryThe aim of this study was to examine whether serum anticholinergic activity (SAA) is a reliable indicator of delirium in the ICU, and whether there is a significant correlation between SAA and quantitative electroencephalographic (EEG) data in delirious patients. In a prospective cohort study, we assessed ICU patients diagnosed with delirium (n = 37). EEG measurements and blood analysis including SAA were performed 48 h following ICU admission. The presence of delirium was evaluated using the Confusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 40 publications
(40 reference statements)
4
41
1
1
Order By: Relevance
“…Indeed, in agreement with previous studies [14], a lower RASS was associated with a lower BIS index in this study. The lower BIS EEG in delirious patients obtained in our present study confirm previous findings using standard and spectral EEG [11,26,27], our previous results using a 16-channel EEG [12], and also in part the results of Ely et al [14] using a monolateral BIS EEG technique.…”
Section: Bis Eegsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, in agreement with previous studies [14], a lower RASS was associated with a lower BIS index in this study. The lower BIS EEG in delirious patients obtained in our present study confirm previous findings using standard and spectral EEG [11,26,27], our previous results using a 16-channel EEG [12], and also in part the results of Ely et al [14] using a monolateral BIS EEG technique.…”
Section: Bis Eegsupporting
confidence: 92%
“…Our previous study on the surgical ICU [12] detected decreased cerebral cortical activity in patients during delirium, measured by a time-consuming 16-channel EEG system. Furthermore, investigating the role of monolateral BIS EEG (ASPECT Medical System) in detecting dementia or delirium produced controversial results [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…(MEND; [111]). Einen wei teren klinischen Therapieansatz zur Be handlung des Intensivdelirs stellt die Ga be von Physostigmin dar, auch wenn bis lang keine Korrelation zwischen anti cholinerger Aktivität im Serum und In tensivdelir nachgewiesen werden konn te [139,140].…”
Section: Medikamentöse Optionenunclassified
“…(16) Characterization of delirium with use of CAM-ICU In the studies using CAM-ICU to detect delirium, mostly in clinical and coronary ICU with critically ill patients it was found that incidence ranged from 14.8% to 89%. (2,8,13,17,21) The condition developed in the first five days (8) in the ICU and lasted from one to three days, (2,20) the length of stay was increased from one to 10 days compared to patients who did not develop delirium. (2,9,21,22) Hypoactive form of delirium was essentially observed in clinical older patients who were MV dependent (51.8%), in comparison to the young (26.6%).…”
Section: Validation Of Cam-icu and Detection Of Delirium In Daily Roumentioning
confidence: 99%